Temporal hemispheric dominance of omge-3: measurement of alpha and beta wave signals using EEG / Afiqah Qumira Ismail - Ismail, Afiqah Qumira (2013)
This paper presents a study of the effect of consuming Omega-3 to the brainwave activity, concentrating on Alpha and Beta waves. The effects were studied through 12 volunteers consisting of 7 male and 5 female Electrical Engineering students. They were supplied with 900 mg of Omega-3 per day for 3 months and the results were concluded. Wireless EEG equipment via blue tooth was used to measure the brainwave signals in the right and left frontal area of the brain with the EEG data recorded from 12 samples. The artifacts of the EEG signals was removed by means of a program using MATLAB and the correlation between the left and the right brainwaves were achieved using paired samples T test from SPSS. The outcomes, which are brain balancing index (BBI) and brain dominance shows the improvement of brain activity after Omega-3 consumption.